Fluorescence microscopy visualization of halomucin, a secreted 927 kDa protein surrounding Haloquadratum walsbyi cells - Zenke, Ralf; von Gronau, Susanne; Bolhuis, Henk; Gruska, Manuela; Pfeiffer, Friedhelm; Oesterhelt, Dieter (Frontiers in Microbiology, 2015)
At the time of its first publication, halomucin from Haloquadratum walsbyi strain HBSQ001 was the largest archaeal protein known (9159 aa). It has a predicted signal sequence, making it likely to be an extracellular or secreted protein. Best BLAST matches were found to be mammalian mucins that protect tissues to dehydration and chemical stress. It was hypothesized that halomucin participates in protection against desiccation by retaining water in a hull around the halophilic organisms that live at the limits of water activity. We visualized Haloquadratum cells by staining their intracellular polyhydroxybutyrate granules using Nile Blue. Halomucin was stained by immunofluorescence with antibodies generated against synthetic peptides derived from the halomucin amino acid sequence. Polyhydroxybutyrate stained cells were reconstructed in 3D which highlights not only the highly regular square shape but also the extreme flatness of Haloquadratum. Double-staining proves halomucin to be extracellular but to be only loosely associated to cells in agreement with its hypothesized function.